Effect of copper salts on the characteristics and antibacterial activity of Cu-modified titanate nanotubes. Issue 6 (December 2020) - Jose, Manu; Szymańska, Karolina; Szymański, Kacper; Moszyński, Dariusz; Mozia, Sylwia
Graphical abstract: Highlights: Cu/TNTs were fabricated using various Cu precursors under ambient or inert atmosphere. Cu-based nanoparticles were dispersed onto TNTs only in case of copper(II) acetate. The reaction atmosphere influenced the ratio of Cu(I):Cu(II). Higher Cu leakage in case of Cu/TNTs obtained under inert conditions. The highest bactericidal activity of hybrid NPs obtained using copper(II) acetate precursor. Abstract: Cu-modified titanate nanotubes (Cu/TNTs) with antibacterial properties were fabricated by a photodeposition approach under two different reaction atmosphere conditions (inert and ambient). Three Cu salts were used as modifying agents: copper(II) acetate, copper(II) sulfate and copper(II) chloride. The physicochemical characterization revealed the occurrence of superfine Cu-based nanoparticles dispersed onto the TNTs modified with copper(II) acetate only. In case of that precursor the highest Cu loading was also obtained. The reaction atmosphere did not affect significantly the amount of Cu deposited onto TNTs; however, it influenced the ratio of Cu(I):Cu(II). That resulted in a higher stability of the samples obtained in the presence of air compared to those obtained under inert conditions, as was found on a basis of Cu release. The antibacterial properties of the Cu/TNTs were investigated against both Gram-positive and Gram-negative bacteria. The hybrid NPs obtained using copper(II) acetate precursor showed the highest bactericidal activity, which was mainly related to the high Cu content in the nanocomposite and the presence of Cu-based NPs.